Tendencias en la producción mundial de arroz - Posada Torres, Rafael (International Center for Tropical Agriculture, 2010)
Trends in world rice production The trends of world rice production, including important variables such as area, production, yields, trade, and international price, are analyzed. World statistics indicate that rice productivity, measured in tons of paddy rice per hectare, has increased over the past 28 years as a result of technological improvements. The world rice supply is now capable of satisfying the demand for this staple without having to increase, in general, the area planted to the crop. During the time period covered by the study, no significant changes were observed in global rice production structure. The quarterly averages of the years 1979-1981 and 1999-2001 were initially compared, and then more recent figures, corresponding to the 2007-2008 growth cycle, were reviewed. Asia continues to be the world’s grain production hub, accounting for nearly 90% of total production worldwide, in other words, more than 600 million tons of paddy rice per year. Although rice is still basically a noncommercial crop at the international level—only 7% of total production is exported—relatively significant changes have occurred in international rice trade figures. Asia has been consolidated as a rice exporter, accounting for 50% of world exports. It is also the region that imports the most rice, accounting for 75% of global imports. These data imply that a high percentage of international rice trade is intra-continental. Net trade figures (imports–exports) confirm this assertion. Africa, in turn, is the only continent that presents a positive financial balance in terms of rice imports. The analysis of recent figures (2007-2008) shows that the economic scenario for rice production will be mainly influenced by exogenous variables such as the increase in the cost of oil, national food security policies, and the aggravation of climate changes, which have triggered an emerging food crisis.